The Pelian ritual in Sebauh district, Bintulu, Sarawak - Tugau, Mangai; Magiman, Mohammad Maulana; Salleh, Norhuda; Mohd Yusoff, Ahmad Nasir; Permana, Septian Aji (Turkish Online Jounal of Qualitative Inquiry, 2021)
Pelian is a healing and a ritual for spirit separation between the dead and the living among the Iban community who strongly believe in Pengarap Lama or Animism. The Pelian ritual has a few objectives: to stop mimpi jai or nightmare, heal the patient, separation of spirit between the dead and the living human, and the process of initiation or ordination for a new Manang or Shaman. Manang can perform the Pelian Ritual based on different objectives, customs, and traditions according to the types of Pelian. The belief towards Pelian ritual started since the Iban believed that the world is divided into three parts: this world, the world of the dead (Sebayan), and the world in the sky. The objective of this research is to explore the ritual process of Pelian and analyse the related symbols. Besides, it is to identify the elements in Pelian that have become an identity to the Iban community. This research was carried out using a qualitative method (ethnography), including field research, participant observation, interviews, and library research. The research area covered Sebauh district, which included Sebauh river, Pandan-Binyo river, Labang river, and Tubau-Jelalong river. The collected data was analysed based on interpretive, descriptive, induction, grounded theory, and the community’s belief and understanding. The findings of this research are that Pelian is a healing ritual to strengthen the Ayu or ‘Life Force of the Soul’ of a person and separate the dead’s soul from the living community. Thus, every Pelian has its functions, and it differs from one another. The appointment of Manang consists of two methods, which are the initiation made by Petara or God through dream and inheritance from parents or other family members. The uniqueness of its process and symbols used in the Pelian ritual has become the Iban community’s identity.